Implementation of a modified incremental conductance MPPT algorithm with direct control based on a fuzzy duty cycle change estimator using dSPACE - Radjai, T.; Rahmani, L.; Mekhilef, Saad; Gaubert, J.P. (Elsevier, 2014)
Maximum power point tracking (MPPT) is a necessary function in all photovoltaic (PV) systems. The classic incremental conductance (IC) MPPT algorithm is widely used in the literature. However, when large changes occur in the irradiance, the performance of this algorithm is degraded. To eliminate all of the disadvantages of the classic IC algorithm, we developed a new IC controller based on a fuzzy duty cycle change estimator with direct control. A fuzzy logic estimator (FLE) is used to estimate the new duty cycle used to track the PV array maximum power point. Compared with the fixed step IC MPPT method with direct control, the proposed algorithm reaches the MPP more accurately and faster during dynamic and steady-state conditions. A controlled Cuk DC-DC converter was implemented and connected to a SunTech STP085B PV panel to verify the accuracy of the proposed method. Matlab/Simulink was used for the simulation studies. Additionally, the algorithms were digitally implemented on the dSPACE ACE1104 platform. The results obtained confirm the advantages of the proposed algorithm. (C) 2014 Elsevier Ltd. All rights reserved.